2018
DOI: 10.1039/c7nj04609j
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional carbon nanomateriels for camptothecine low-water soluble anticancer drug delivery

Abstract: A multifunctional hybrid nanomaterial of magnetic graphene oxide (GO) and magnetic carbon nanotubes (CNTs) was ensheathed with mesoporous silica, for the loading and delivery of an anticancer drug, camptothecine (CPT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It was observed that GQDs were biocompatible and the biotin-linked GQDs loaded with DOX proved to have greater uptake rather than free DOX or GQDs-DOX in A549 cell line. 47 A system based on decorated magnetic nanoparticles onto GO layered by mesoporous silica was developed for camptothecin (CPT) delivery. The carriers have a capacity of 20% regarding drug loading and showed a controlled and pH-responsive drug release.…”
Section: Dovepressmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed that GQDs were biocompatible and the biotin-linked GQDs loaded with DOX proved to have greater uptake rather than free DOX or GQDs-DOX in A549 cell line. 47 A system based on decorated magnetic nanoparticles onto GO layered by mesoporous silica was developed for camptothecin (CPT) delivery. The carriers have a capacity of 20% regarding drug loading and showed a controlled and pH-responsive drug release.…”
Section: Dovepressmentioning
confidence: 99%
“…To be specific, smaller flakes showed less toxicity. 47 Considering the size of graphene is also important to think about the mechanism by which the material internalizes into a target cell. 16 Overall, regarding the presented information, it is worthwhile noting that examining a study concerned with graphenebased materials, many factors and properties including size of the material, shape, functionalization, functionalizing groups and percent of these reactions, in-vivo concentration, pharmacokinetic and pharmacodynamics of the materials must carefully be considered.…”
Section: Future Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, magnetic GO and magnetic CNTs were ensheathed with mesoporous silica, for the loading and delivery of CPT. The complex of prepared nanomaterials and CPT evinced remarkably high cytotoxicity towards HeLa cell lines compared to the pure drug …”
Section: Applications Of Carbon Nanomaterials In the Cancer Therapymentioning
confidence: 99%